Method for desulfurizing lithium slag through cooperation of hydrothermal method and CO2 conversion
The lithium slag is desulfurized through hydrothermal synergistic CO2 conversion method, which solves the problems of low desulfurization efficiency and environmental protection of lithium slag, and realizes the synergistic process of efficient desulfurization and CO2 conversion, which improves the utilization value and economic benefits of lithium slag.
Patent Information
- Application Number
- CN202510076998.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
AI Technical Summary
With the development of lithium resources, the comprehensive utilization of lithium slag has become an urgent problem to be solved. The existing lithium slag desulfurization technology is low in efficiency and high in cost, and the demand for environmental protection and resource recycling is still not fully met.
The lithium slag is desulfurized by hydrothermal synergistic CO2 conversion method. The hydrothermal reaction environment is formed through particle size screening, slurry pH, temperature and liquid-solid ratio and other conditions, which promotes the removal of sulfur components in the lithium slag, and the desulfurization solution is treated with CO2 to realize the coordinated process of lithium slag desulfurization and CO2 conversion.
This method efficiently removes sulfur from lithium slag, retains other effective components such as calcium, and increases the added value of desulfurized lithium slag. It also absorbs and converts CO2-containing industrial waste gas by utilizing alkaline waste liquid and low-temperature waste heat, realizes coordinated resource recycling, disposal and carbon emission reduction, reduces treatment costs and improves economic benefits.
Smart Images

Figure CN119870098A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium slag treatment and solid waste resource utilization and carbon emission reduction, and in particular to a method for desulfurizing lithium slag by hydrothermal coordinated CO2 conversion. Background Art
[0002] my country has relatively abundant lithium resources, which are mainly distributed in Qinghai and Tibet (salt lake lithium), Sichuan (spodumene mines) and Jiangxi (lepidolite mines). At present, my country's proven lithium resources are mainly hard rock lithium mines. With the development of lithium resource development technology, the process of extracting lithium resources from hard rock lithium mines by sulfate roasting is becoming more and more common, resulting in an increasing amount of sulfur-containing lithium slag emissions. Desulfurization treatment of lithium slag can better realize the resource utilization of lithium slag.
[0003] At present, the main technologies for lithium slag desulfurization are flotation desulfurization and thermochemical desulfurization. For example, Chinese patent CN108147658B targets the tailings after lithium extraction from spodumene by sulfuric acid method, adds dispersant and collector, and undergoes gravity selection or flotation or gravity selection and flotation combination process to obtain pyrophyllite raw material for glass fiber after desulfurization. Patent CN114226413B first grinds lithium slag, and then undergoes weak magnetic separation, strong magnetic separation and flotation to obtain sulfur-containing tailings and flotation materials. The desulfurized materials are processed to prepare silicon aluminum powder. Patent CN113976309B uses lithium slag to comprehensively recover lithium, tantalum niobium, silicon aluminum powder, iron concentrate and gypsum. It also adopts flotation desulfurization after adding collector, and finally removes sulfur from lithium slag raw materials in the form of gypsum. In terms of thermochemical desulfurization, patent CN110482894B mixes acid lithium slag powder and fat coal powder, performs heat treatment at 700℃-900℃, and the holding time is 100-150 minutes. The desulfurization rate is up to 63.6%. The lithium slag powder after desulfurization is used to replace cement in concrete. Patent CN118026239A discloses a method of mixing lithium slag with an inorganic acid composite reagent, obtaining a desulfurized and decalcified solution and a desulfurized and decalcified slag after a catalytic dissociation reaction, adding a salt inducer to the desulfurized and decalcified solution, and crystallizing at low temperature to obtain fine grains such as calcium sulfate, and finally realizing the resource utilization of lithium slag desulfurization and decalcification.
[0004] In summary, with the development of lithium resources, the comprehensive utilization of lithium slag has become an urgent problem to be solved. Lithium slag desulfurization is an important link in the resource utilization of lithium slag. The development of high-efficiency, low-cost and easy-to-operate lithium slag desulfurization technology is of great significance to the environmental protection and resource recycling of lithium resource development. Summary of the invention
[0005] The purpose of the present invention is to provide a method for desulfurizing lithium slag by hydrothermal synergistic CO2 conversion. The method forms a hydrothermal reaction environment by particle size screening, adjusting slurry pH, temperature, liquid-to-solid ratio and other conditions, thereby promoting the removal of sulfur from the lithium slag. At the same time, the lithium slag desulfurization solution is treated with CO2 to synergistically convert CO2, thereby simultaneously realizing the process of lithium slag desulfurization and CO2 conversion.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] Step a, grinding the lithium slag obtained after extracting lithium from the lithium mica concentrate roasted by sulfate method through a lithium leaching process, and screening the ground lithium slag;
[0008] Step b, according to the particle size of the lithium slag after screening, respectively prepare slurries of lithium slags of different particle sizes, transport them to the reactor, adjust the material-liquid ratio, and adjust the pH of the slurry;
[0009] Step c, setting the reaction temperature and reaction time in the reactor, starting the hydrothermal reaction, introducing CO2 gas, and stirring the reaction process;
[0010] Step d, after the reaction time is over, solid-liquid separation is performed, and the solid is dried to obtain desulfurized lithium slag. CO2 gas is continued to be introduced into the solution after separation to achieve solution pretreatment and CO2 synergistic conversion. The pretreated solution can be reused in step b.
[0011] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. By controlling the following technical parameters, the technical objectives and beneficial effects of the present invention can be better achieved.
[0012] Preferably, the particle size of the lithium slag after grinding in step a is 60 mesh to 250 mesh.
[0013] Preferably, the liquid used for preparing the slurry in step b is alkaline waste liquid or alkaline solid waste leaching liquid such as metallurgical slag, the solid-liquid ratio is 1:10-30, and the pH of the slurry after adjustment is 7-13.
[0014] Preferably, the reaction temperature in step c is between 20° C. and 95° C., the reaction time is 5 min to 30 min, and the stirring method is mechanical paddle stirring or electromagnetic stirring.
[0015] Preferably, the slurry temperature in step c can be recovered by using waste heat as a heating source.
[0016] Preferably, the solid-liquid separation method in step d is sedimentation, filtration or centrifugation.
[0017] Preferably, the CO2 gas introduced in step d is pure CO2 gas or industrial waste gas containing CO2.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The present invention provides a method for desulfurizing lithium slag by hydrothermal coordinated CO2 conversion. The method utilizes hydrothermal reaction, screens the lithium slag particle size, and correspondingly controls and adjusts the slurry pH, temperature, liquid-to-solid ratio and other conditions to form a hydrothermal reaction environment, thereby promoting the removal of sulfur from the lithium slag, and utilizes CO2 to treat the lithium slag desulfurization solution, thereby simultaneously achieving lithium slag desulfurization and CO2 conversion.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The method of the present invention controls the hydrothermal reaction condition parameters according to the particle size of the lithium slag, efficiently removes the sulfur in the lithium slag, and retains other effective components such as calcium required for large-scale utilization of the lithium slag in the field of building materials, thereby increasing the added value of the desulfurized lithium slag.
[0022] (2) The method of the present invention can utilize alkaline solid waste such as alkaline waste liquid or metallurgical slag, and can utilize low-temperature waste heat as a heat source. At the same time, it can absorb and transform industrial waste gas containing CO2, thereby realizing coordinated resource recovery, disposal and utilization and carbon emission reduction.
[0023] (3) The method of the present invention has a simple process, the process is easy to operate and control, the reaction conditions are mild, and other waste resources can be synergistically disposed of and utilized, thereby reducing processing costs and improving economic benefits while achieving good social and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a process flow chart of the method for desulfurizing lithium slag by hydrothermal coordinated CO2 conversion provided by the present invention. DETAILED DESCRIPTION
[0025] The technical scheme of the present invention and the technical effects produced are further described in detail below through specific examples. The following examples are typical but non-limiting examples of the method of the present invention. The lithium slag used in the examples is taken from a lithium extraction production enterprise of sulfate process in Jiangxi.
[0026] Example 1
[0027] A method for desulfurizing lithium slag by hydrothermal synergistic CO2 conversion, the steps are as follows:
[0028] 5 g of 250-mesh lithium slag was selected and placed in a high-pressure reactor, 100 g of steel slag leaching solution was added, the pH value of the test solution was 11.63, the high-pressure reactor was opened, the temperature of the reactor was adjusted to 30°C, and the reaction was stirred for 15 min, and CO2 gas was continuously introduced.
[0029] After the reaction, the solution was filtered to obtain the desulfurized lithium slag solid and dried. The sulfur content of the desulfurized lithium slag was tested to be 4.16% (in terms of SO3), the sulfur content of the original 250 mesh lithium slag was 14.30% (in terms of SO3), and the desulfurization rate was 70.91%.
[0030] Example 2
[0031] 5 g of 250-mesh lithium slag was placed in a high-pressure reactor, 150 g of waste alkali solution was added, the pH value of the test solution was 12.72, the high-pressure reactor was opened, the temperature of the reactor was adjusted to 90°C, and the reaction was stirred for 30 min, and CO2 gas was continuously introduced.
[0032] After the reaction, the solution was centrifuged to obtain the desulfurized lithium slag solid and dried. The sulfur content of the desulfurized lithium slag was tested to be 3.49% (in terms of SO3), the sulfur content of the original 250-mesh lithium slag was 14.30% (in terms of SO3), and the desulfurization rate was 75.59%.
[0033] Example 3
[0034] 5 g of 60-mesh lithium slag was selected and placed in a high-pressure reactor. 50 g of steel slag leaching solution was added. The pH value of the test solution was 10.55. The high-pressure reactor was opened and the temperature of the reactor was adjusted to 60°C. The reaction was stirred for 25 min and CO2 gas was continuously introduced.
[0035] After the reaction, the solution was centrifuged to obtain the desulfurized lithium slag solid and dried. The sulfur content of the desulfurized lithium slag was tested to be 3.02% (in terms of SO3), the sulfur content of the 60-mesh lithium slag original sample was 8.65% (in terms of SO3), and the desulfurization rate was 65.09%.
[0036] Example 4
[0037] 5 g of 120-mesh lithium slag was selected and placed in a high-pressure reactor, 100 g of waste alkali solution was added, the pH value of the test solution was 10.78, the high-pressure reactor was opened, the temperature of the reactor was adjusted to 90°C, and the reaction was stirred for 30 min, and CO2 gas was continuously introduced.
[0038] After the reaction, the solution was filtered to obtain the desulfurized lithium slag solid and dried. The sulfur content of the desulfurized lithium slag was tested to be 4.07% (in terms of SO3), the sulfur content of the original 120-mesh lithium slag was 13.03% (in terms of SO3), and the desulfurization rate was 68.76%.
[0039] Example 5
[0040] 5 g of 200-mesh lithium slag was selected and placed in a high-pressure reactor, 150 g of waste alkali solution was added, the pH value of the test solution was 11.34, the high-pressure reactor was opened, the temperature of the reactor was adjusted to 60°C, and a stirring reaction was carried out. The reaction time was 30 min, and CO2 gas was continuously introduced.
[0041] After the reaction, the solution was filtered to obtain desulfurized lithium slag solid and dried. The sulfur content of the desulfurized lithium slag was tested to be 3.60% (in terms of SO3), the sulfur content of the original 200-mesh lithium slag was 13.65% (in terms of SO3), and the desulfurization rate was 73.63%.
[0042] Example 6
[0043] 5 g of 120-mesh lithium slag was selected and placed in a high-pressure reactor, 50 g of steel slag leaching solution was added, the pH value of the test solution was 10.56, the high-pressure reactor was opened, the temperature of the reactor was adjusted to 50°C, and the reaction was stirred for 15 min, and CO2 gas was continuously introduced.
[0044] After the reaction, the solution was filtered to obtain the desulfurized lithium slag solid and dried. The sulfur content of the desulfurized lithium slag was tested to be 3.94% (in terms of SO3), the sulfur content of the original 120-mesh lithium slag was 13.03% (in terms of SO3), and the desulfurization rate was 69.76%.
[0045] Comparative Example 1
[0046] A method for desulfurizing lithium slag, comprising the following steps:
[0047] 5 g of 120-mesh lithium slag was placed in a high-pressure reactor, 150 g of deionized water was added, the pH value of the test solution was 7.06, the high-pressure reactor was opened, the temperature of the reactor was adjusted to 60°C, and a stirring reaction was carried out. The reaction time was 120 min, and CO2 gas was continuously introduced.
[0048] After the reaction, the solution was filtered to obtain desulfurized lithium slag solid and dried. The sulfur content of the desulfurized lithium slag was tested to be 5.21% (in terms of SO3), the sulfur content of the original 120-mesh lithium slag was 13.03% (in terms of SO3), and the desulfurization rate was 60.02%.
[0049] Comparative Example 2
[0050] A method for desulfurizing lithium slag, comprising the following steps:
[0051] 5 g of 250-mesh lithium slag was selected and placed in a high-pressure reactor, 100 g of deionized water was added, the pH value of the test solution was 7.11, the high-pressure reactor was opened, the temperature of the reactor was adjusted to 90° C., and a stirring reaction was carried out, wherein the reaction time was 15 min.
[0052] After the reaction, the solution was filtered to obtain the desulfurized lithium slag solid and dried. The sulfur content of the desulfurized lithium slag was tested to be 6.07% (in terms of SO3), the sulfur content of the original 250-mesh lithium slag was 14.30% (in terms of SO3), and the desulfurization rate was 57.55%.
[0053] It can be seen from the above embodiments and comparative examples that the method of the present invention adjusts the slurry pH, temperature, liquid-solid ratio and other conditions according to the particle size of the lithium slag to form a hydrothermal reaction system, thereby promoting the removal of sulfur from the lithium slag. By utilizing alkaline solid waste such as alkaline waste liquid or metallurgical slag, low-temperature waste heat is used as a heat source to absorb and transform industrial waste gas containing CO2, and simultaneously achieve resource collaborative recovery, disposal and utilization and carbon emission reduction. The method has a simple process, easy operation and control of the process, mild reaction conditions, and can be used in a collaborative manner to dispose of and utilize other waste resources, thereby reducing processing costs and improving economic benefits, and has broad application prospects.
[0054] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for desulfurizing lithium slag by hydrothermal synergistic CO2 conversion, characterized in that: The following steps are involved: Step a, grinding the lithium slag and screening the ground lithium slag; the lithium slag is obtained by roasting lithium mica concentrate by sulfate method and extracting lithium through lithium leaching process; Step b, according to the particle size of the lithium slag after screening, respectively prepare slurries of lithium slags of different particle sizes, transport them to the reactor, adjust the material-liquid ratio, and adjust the pH of the slurry; Step c, setting the reaction temperature and reaction time in the reactor, starting the hydrothermal reaction, introducing CO2 gas, and stirring the reaction process; Step d, after the reaction time is over, solid-liquid separation is performed, and the solid is dried to obtain desulfurized lithium slag, and CO2 gas is continued to be introduced into the solution after separation to achieve solution pretreatment and CO2 synergistic conversion, and the pretreated solution can be reused in step b.
2. The method according to claim 1, characterized in that: The particle size of the lithium slag after grinding in step a is 60 mesh to 250 mesh.
3. The method according to claim 1, characterized in that The liquid used for preparing the slurry in step b is alkaline waste liquid or alkaline solid waste leaching liquid such as metallurgical slag, the solid-liquid ratio is 1:10-30, and the pH of the slurry after adjustment is 7-13.
4. The method according to claim 1, characterized in that: The reaction temperature in step c is between 20° C. and 95° C., the reaction time is 5 min to 30 min, and the stirring method is mechanical paddle stirring or electromagnetic stirring.
5. The method according to claim 4, characterized in that The slurry temperature can be increased by recovering waste heat as a heating source.
6. The method according to claim 1, characterized in that The solid-liquid separation method in step d is sedimentation, filtration or centrifugation.
7. The method according to claim 1, characterized in that The CO2 gas introduced in step d is pure CO2 gas or industrial waste gas containing CO2.
Citation Information
Patent Citations
Method for producing lithium carbonate through flue gas mineralization of aluminum-lithium slag
CN115304086A
Process for extracting lithium carbonate through ore phase reconstruction of lepidolite
CN116119692A
Roasting lithium slag production process method based on industrial processing
CN117361585A
KR20210131094A